Elections and Governance in Nigerias Fourth Republic - Agbu, Osita (Book collections on Project MUSE., 2016)
Elections and Governance in Nigeria's Fourth Republic is a book about Nigerian politics, governance and democracy. It at once encompasses Nigeria's post-colonial character, its political economy, party formation since independence, the role of Electoral Commissions, as well as, in depth analyses of the 1999, 2003 and 2007 general elections that involved extensive fieldwork. It also presents aspects of the 2011 and 2015 general elections, while discussing the state of democratic consolidation, and lessons learned for achieving good governance in the country. It is indeed, a must read for students of politics, academics, politicians, statesmen and policy makers, and in fact, stakeholders in the Nigerian democracy project. The book stands out as a well-researched and rich documentary material about elections in Nigeria, and the efforts so far made in growing democracy.